CAREGIVERS' ATTITUDES TOWARD AGING: PROTECTIVE FACTOR IN DEMENTIA CAREGIVING. (11th November 2018) - Kim, E; Bolkan, C
Abstract: Dementia caregiving can lead to detrimental health outcomes and greater risks for morbidity and mortality (Roth, Fredman, & Haley, 2015). Accordingly, it is significant for dementia caregivers to engage in health-promoting behaviors which contribute to buffering negative caregiving experiences. Studies found that positive aging attitudes predict preventive health behaviors while negative aging attitudes are related to adverse health outcomes (Levy & Myers, 2004; Freeman et al., 2015). The purpose of this study was to investigate the relationships between caregivers' aging attitudes and their health behaviors/outcomes. We also examined the impact of caregivers' aging attitudes on quality of care. Dementia caregivers (N = 99, mean age = 54) answered an online survey that included information about their attitudes toward aging, physical and mental health, levels of physical activity, and perceptions about dementia care. Caregivers' positive attitudes toward aging were associated with better overall health condition (β = .49, p < .005), better emotional health (β= .56, p < .001), and higher levels of physical activity (β= .84, p < .05). Caregivers' positive aging perceptions was also associated with self-efficacy for managing dementia (β = 1.44, p < .005) and willingness to provide better dementia care (β = .73, p < .05). In short, caregivers with positive attitudes toward aging adapted and coped more successfully with caregiving than those with negative attitudes toward aging. Also, positive aging attitudes may contribute to care recipients' well-being if provided with better dementia care. Education targeting caregivers' aging attitudes is needed to promote well-being in caregivers.